The Importance of Institutional Culture in Production of Integrated Development Plans: The Case of City of Johannesburg - Mothiba, Machebane Roslyn (My University, 2006)
The research recognises the IDP as an important post-apartheid planning tool that can potentially lead to integration within the City of Johannesburg. However, for the IDP to attain its mandated goals, an enabling institutional culture of the City and its units need to prevail. The gap/challenge is that the institutional culture of the City and its departments/units are shaped by Joburg 2030, a purely economic strategy that does not embrace the principles needed for attainment of IDP goals. The principles needed for successful formulation and implementation of the IDP are found in equity planning theories and New Institutionalism. These are the principles that do not form part of the Joburg 2030 vision. The solution is for the Joburg 2030 to include the planning principles as already highlighted. This solution will affect departmental practices for the better.
Student Number : 0005386G - MSc research report - School of Architecture and Planning - Faculty of Engineering and the Built Environment
Keywords: IDP; post-apartheid planning; Johannesburg; institutional culture; equity planning theories; New Institutionalism